Dietary fat induces sustained reward response in the human brain without primary taste cortex discrimination - Tzieropoulos, Hélène; Rytz, Andreas; Hudry, Julie; Le Coutre, Johannes (Frontiers in Human Neuroscience, 2013)
To disentangle taste from reward responses in the human gustatory cortex, we combined high density electro-encephalography with a gustometer delivering tastant puffs to the tip of the tongue. Stimuli were pure tastants (salt solutions at two concentrations), caloric emulsions of identical taste (two milk preparations differing in fat content) and a mixture of high fat milk with the lowest salt concentration. Early event-related potentials showed a dose-response effect for increased taste intensity, with higher amplitude and shorter latency for high compared to low salt concentration, but not for increased fat content. However, the amplitude and distribution of late potentials were modulated by fat content independently of reported intensity and discrimination. Neural source estimation revealed a sustained activation of reward areas to the two high-fat stimuli. The results suggest calorie detection through specific sensors on the tongue independent of perceived taste. Finally, amplitude variation of the first peak in the event-related potential to the different stimuli correlated with papilla density, suggesting a higher discrimination power for subjects with more fungiform papillae.